Corrosion Analysis in Different Cookware Materials - Martìnez-Gomez, Javier (2021)
Efficient use of energy is the main concern during the implementation of technology migration processes because several factors must be taken into account for this purpose. In this paper, the migration process from cookers based on liquefied petroleum gas (LPG) to electric induction stoves is presented. To accomplish this study, several tests have been performed in three kinds of pots made from different materials: stainless steel, enameled cast iron, and aluminum. The purpose of these tests is to see how different materials for cookware would be affected by introducing them into a salt spray chamber. Indeed, the tests try to reach similar conditions that cooking with salt. The achieved results try to emphasize the selection, in terms of corrosion, of the best material for suitable cookware production applied in induction stoves. The methods established in the standard ASTM B895 – 05 have allowed to accurately evaluate the corrosion property. A wrong choice of materials can lead to an inadequate life cycle assessment of pots. After completing this research, it has been found that enameled cast iron and stainless-steel show higher corrosion resistances.